Living labs opened dialogues about antibiotic use in dairy cattle and pig sectors - Insights from a Danish case study based on participatory action research - Mette Vaarst; Merete Studnitz; Mogens Agerbo Krogh; Hanne Kongsted (Acta Veterinaria Scandinavica)
Abstract Background Prudent antimicrobial use (AMU) is paramount for future sustainable animal production. Continuous efforts are required to have a low and well-regulated AMU. Living Labs (LLs) are multistakeholder open innovation platforms that have the potential to allow multiple stakeholders to explore common ground, create dialogues and find solutions to jointly identified problems. The purpose of this study was to stimulate multistakeholder dialogues leading to transitions towards a more prudent AMU in the Danish dairy and pig sectors. Results The two LLs, which focused on pig farms and dairy cattle farms, worked in parallel for 30 months. Stakeholders in the pig and dairy sectors pointed to systemic structures such as logistic conditions and global market structures as the main drivers of the current AMU. Both LLs expressed conflicting interests and perceptions around the concept of prudent AMU related to animal welfare and today’s production systems. Thus, the LLs in the Danish context became spaces for opening dialogues and negotiating difficult and sensitive issues in addition to being open-innovation platforms. Both LLs expressed scepticism around the connections between AMU in animal farming and the global threat of antimicrobial resistance to humans. However, this scepticism was more dominant for the stakeholders of the pig sector. The feeling of being a global front-runner in prudent AMU, legislation and transparent monitoring of AMU existed in both sectors, but both LLs identified possibilities and room for improvement. The need to reduce AMU was most consistently articulated in the dairy cattle LL, where the stakeholders increasingly focused on calves from dairy farms and the systemic drivers, which made it challenging to reduce AMU. Some actors in the pig LL kept questioning whether a change towards more prudent AMU was needed in Denmark. Conclusion The LL approach fostered important dialogues and insights between central stakeholders in the sectors and was thereby helpful in terms of opening and contributing to dialogues about antibiotic usage in dairy cattle and pigs within and across sectors.